INTERPRETASI STRUKTUR PENGONTROL MANIFESTASI PANASBUMI GEDONGSONGO DI LERENG SELATAN GUNUNGAPI UNGARAN DENGAN DATAMAGNETIK - SARI, RENA JUWITA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Gunung Ungaran is a volcano located in the Central Java province, Indonesia, about 30 km southwest of Semarang city. This volcano has several areas with geothermal manifestations. Gedongsongo manifestation is among them. This manifestation is located on the southern slope Ungaran volcano, at 110°20‟27” Eand 07°14‟3” S. A geomagnetic survey has been done in Gedongsongo area to understand the geologic structure that controls the manifestation. The study area covers about 3.5 x 4